PENGGUNAAN MEDIA CONGKLAK UNTUK MENINGKATKAN PEMAHAMAN KONSEP PENJUMLAHAN DAN PENGURANGAN PADA SISWA KELAS I SEKOLAH DASAR - Ningsih; Din Azwar Uswatun; Arsyi Rizqia Amalia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low understanding of basic mathematical concepts, particularly addition and subtraction, among lower-grade students, which is often caused by conventional learning methods and the lack of use of concrete media. The purpose of this study is to improve the understanding of addition and subtraction concepts in first-grade elementary school students through the use of the traditional congklak game. The type of research used is Classroom Action Research (CAR), implemented in two cycles using the Kemmis and McTaggart model. The research subjects involved 20 first-grade students of Lembursawah State Elementary School in the even semester of the 2025/2026 academic year. Data were collected through testing techniques, observations of teacher and student activities, and documentation. The indicator of success is determined if >80% of students achieve the Minimum Completion Criteria (KKM) of 70. The results of the study show a consistent improvement in the quality of learning and student learning outcomes. The average class score increased gradually from 65 in the Pre-Cycle, to 71 in Cycle I, and reached 76 in Cycle II. Students' classical learning achievement significantly increased from 25% (5 students) in the pre-cycle to 50% (10 students) in Cycle I, and then reached a peak of 85% (17 students) in Cycle II. This final result successfully exceeded the established classical success indicator target. Based on these results, it can be concluded that the use of traditional congklak card-based game media is effective in improving the understanding of addition and subtraction concepts in first-grade elementary school students. Keywords: Congklak Media, Mathematical Concept Understanding, Elementary School.